2019
DOI: 10.4103/ua.ua_90_18
|View full text |Cite
|
Sign up to set email alerts
|

Modification of microsurgical longitudinal intussusception technique of vaso-epididymal anastomosis: A single-center experience

Abstract: Purpose:Microsurgical intussusception vasoepididymostomy (VE) is well-established treatment option for obstructive azoospermia due to epididymal obstruction. In this study, we evaluated patency rates and complications of our modified longitudinal intussusception technique of microsurgical VE. We have modified the intussusception technique by taking only adventitia of epididymal tubule.Methods:This was a prospective, single-center (tertiary care center) study conducted from February 2008 to January 2016. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…All included studies were published between 1978 and 2021, with a cohort size ranging from 8 to 255 patients. Among them, 16 studies were conducted in China, five in Japan, 15 in America, four in India, two in Korea, two in Sweden, two in Saudi Arabia, one in Canada, one in Belgium, one in Egypt, one in Romania, and one in Slovenia, 4–9,12–56 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were published between 1978 and 2021, with a cohort size ranging from 8 to 255 patients. Among them, 16 studies were conducted in China, five in Japan, 15 in America, four in India, two in Korea, two in Sweden, two in Saudi Arabia, one in Canada, one in Belgium, one in Egypt, one in Romania, and one in Slovenia, 4–9,12–56 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 4 shows different patency criteria for the patency rate. The mean patency rate was 65% (95% CI, 59–71%) when the patency criterion was the presence of any sperm in the semen [ 3 , 6 , 13 , 16 , 17 , 20 , 22 , 24 , 27 , 28 , 30 ]. When the patency criterion was sperm concentration >10 thousand/ml [ 4 , 5 , 11 , 15 , 21 , 25 , 26 ] or >1 million /ml [ 7 , 8 ], the mean patency rate was 71% (95% CI, 65–77%) and 69% (95% CI, 42–95%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 489 articles identified, 24 studies were eligible and included in the meta-analysis [3][4][5][6][7][8][9][10][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This study's identification and selection process is illustrated in Fig 1 (S1 and S2 Files), according to the PRISMA flow chart.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…The two-suture intussusception technique of a VEA was first described by Marmar [13] in 2000, and they reported a patency rate of 81.3% in 16 patients. Since then, many modifications have been described, with patency rates ranging from 48% to 81% [6] , [14] , [15] , [16] , [17] . In the present study, we found an overall patency rate of only 36.5%, with 46% patency in patients undergoing bilateral surgery.…”
Section: Discussionmentioning
confidence: 99%